2016
DOI: 10.1016/j.ceramint.2016.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Sarawak and Gladstone fly ash to produce geopolymers: A physical, chemical, mechanical, mineralogical and microstructural analysis

Abstract: Two types of fly ash sourced from Sarawak, Malaysia and Gladstone, Australia reflect differences in chemical compositions, mineral phase and particle size distributions. In this paper, the Sarawak fly ash was used to produce geopolymer in comparison to the welldeveloped Gladstone fly ash-based geopolymer. Characteristics of fly ash and mixtures proportions affecting compressive strength of the geopolymers were investigated. It is found that the variations of both fly ash types on particle size distributions, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The glass’s chemical composition may prompt the high reactivity of high-calcium FAs. According to previous research findings, more than 188 mineral groups and 316 individual minerals are recognized in FAs [ 101 , 110 ], and the glass composition in high- and low-calcium FAs differ from each other. The mineral composition is commonly more multifaceted in high-calcium FAs, which has been identified to have large volumes of crystalline C 3 A (4–8%), CaO (1–2.5%), and C 4 A 3 S (1–2.5%) than in low-calcium FAs [ 111 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The glass’s chemical composition may prompt the high reactivity of high-calcium FAs. According to previous research findings, more than 188 mineral groups and 316 individual minerals are recognized in FAs [ 101 , 110 ], and the glass composition in high- and low-calcium FAs differ from each other. The mineral composition is commonly more multifaceted in high-calcium FAs, which has been identified to have large volumes of crystalline C 3 A (4–8%), CaO (1–2.5%), and C 4 A 3 S (1–2.5%) than in low-calcium FAs [ 111 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Sarawak fly ash has been successfully used in a handful of studies (Leong et al 2015;Leong et al 2016a;Leong et al 2016b). Table 1 shows the chemical compositions of the fly ash using WD-X-ray Fluorescence Spectrometer (WD-XRF).…”
Section: Fly Ashmentioning
confidence: 99%
“…SEM results of previous studies show that the workability of the geopolymer binders is influenced by the particle size and shape of the precursor which may also influence the performance of the binder. The study by [76] considered the morphology of two types of PFA geopolymers and reported that PFAs with more rounded particles showed improved workability at a lower activator liquid-PFA ratio due to the shape of the PFA grains. This cenospherical particle shape enhances the ball bearing effect which allows easy mixing of soils and may have resultant effect on the strength of the stabilised soils.…”
Section: Effects Of Alkali Activator Type On Microstructure and Strength Of Geopolymers Bindersmentioning
confidence: 99%